การพัฒนาระบบทดสอบออนไลน์เพื่อวินิจฉัยมโนทัศน์ที่คลาดเคลื่อนทางคณิตศาสตร์ด้วยแบบสอบวินิจฉัยสี่ระดับแบบใหม่ - วีรวัฒน์ โอษฐงาม (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The objective of this research was to 1) compare diagnostic results of the three-tier and the new four-tier diagnostic test in diagnosing mathematic misconception, 2) analyze the congruence among diagnostic results from the three-tier, the new four-tier diagnostic test and think-aloud interview, 3) develop and, 4) validate the online testing system for diagnosing mathematic misconception. The development was separated into three phases: developing and validating the psychometric properties of the three-tier and the new four-tier diagnostic tests for diagnosing mathematic misconception; developing the online testing system for the new four-tier mathematic misconception diagnostic test; and, validating the online testing system for diagnosing mathematic misconception. The participants in this new four-tier diagnostic testing were 60 eleventh-grade students. The research instruments were the interview form, the three-tier diagnostic test, the new four-tier diagnostic test, the user’s interface online testing system form, and the user’s experience form. The data were analyzed using descriptive statistics, a difficulty index, a discrimination index, reliability, Pearson’s correlation, and criterion-related validity.The research findings were as follows:1. The results of the study showed both a high correlation level of Pearson correlation coefficient (r=0.976) between the three-tier and the new four-tier diagnostic test statistics significant at the .01 level.2. The correlation between the diagnostic results of the new four-tier diagnostic test and the think-aloud interview was not different to the results of the three-tier diagnostic and the think-aloud interview.3. The system development results indicated that there were three stages to the operating system 1) registering for the testing system 2) taking the test and 3) reporting the test results.4. The user’s interface online testing system results from the experts showed that the system was adequate in all four aspects, with the highest evaluation for the clear explicitly of the system manual. The user experience survey also revealed that the users were most satisfied with the friendly and transparent design of the system.